Acral malignant melanoma in pregnancy: a case report (Portuguese Journal of Family Medicine and General Practice, 2025)
The incidence of malignant melanoma is increasing dramatically, being one of the most common neoplasms during pregnancy and with high metastatic potential. Most develop in pre-existing pigmented nevi and the hyperpigmentation of pregnancy contributes to delayed diagnosis. Depths greater than one millimeter, ulceration and/or mitosis, and metastasis are associated with poor prognosis. Metastasis to the placenta and fetus is extremely rare. This clinical case selection aimed to raise awareness of the importance of identifying suspicious skin lesions early. The case concerns a 33-year-old pregnant woman, at 36 weeks of gestation, who went to the Family Health Unit due to an ulcerated lesion, difficult to heal, on the first toe of the left foot, with a gradual evolution of six months, which she associated with local trauma. On objective examination, it was observed a pigmented lesion of three centimeters, with irregular borders and heterogeneous coloration, and with a pericentimetric focal area of ulceration. Due to clinical suspicion of malignant melanoma, an urgent hospital consultation for teledermatological screening was requested. During the consultation, incisional skin biopsy and inguinal ultrasonography with cytopuncture of suspicious adenomegaly were performed. The patient underwent disarticulation of the first toe of the left foot and left inguinal dissection, which revealed a seven-millimeter thick acrolentiginous melanoma and micrometastases in two lymph nodes. The remaining imaging study did not show other secondary lesions. It was established the diagnosis of malignant melanoma classified as pT4bN2bM0, stage IIIC, with an indication for adjuvant immunotherapy, but poor prognosis. Thus, the case described emphasizes the importance of instilling our pregnant women (and others) to perform regular skin self-examination. It is up to us to carry out a thorough skin examination, especially in the presence of multiple pigmented nevi, allowing for timely detection, referral, and diagnosis and, therefore, access to potentially curative therapies.
Keywords: Malignant melanoma; Pregnancy